System perspective on cleaner technologies for renewable methane production and utilisation towards carbon neutrality: Principles, techno-economics, and carbon footprints. (1st November 2022) - Qi, Meng; Liu, Yi; He, Tianbiao; Yin, Liang; Shu, Chi-Min; Moon, Il
Highlights: An integral overview of the renewable methane economy. Overview of system developments for renewable methane production and utilisation. Techno-economic assessments and carbon footprints of cleaner technologies. Challenges and opportunities to fully decarbonise renewable methane systems. Abstract: Decarbonisation of the production and utilisation of natural gas (NG) is the main force behind attempts to reach climate targets because NG is one of the most dominant fuels in the energy and transportation sectors. In the transition to a carbon-neutral society, steps must be defined towards achieving cleaner production and utilisation of NG and towards post-combustion carbon capture to create a completely closed carbon cycle. Methane produced using renewable energy sources is a sustainable substitute for NG and is crucial to accelerating the penetration of the current energy infrastructure by renewables. Supported by existing gas transportation networks, renewable methane (RM) is both an energy storage medium and an advanced fuel that can be used in areas that are considered difficult to electrify. The present article is a state-of-the-art review of RM and a range of clean technologies from production to end-use and carbon capture, which are necessary to minimise lifecycle carbon emissions. The techno-economics and challenges of replacing NG with RM are emphasised. The focal research points for a future RM economy with respect to systems design are highlighted, and the novel renewable-powered technologies that are required to promote net-zero emissions are summarised. Although employing RM is not economically feasible, trends towards carbon emission limitations, carbon taxes, and renewables subsidies will make RM cost-competitive with NG. In view of the state-of-the-art technologies, future research is expected to develop energy- and cost-effective production and utilisation solutions for enhancing the feasibility of RM.